ANALISA ASAM ORGANIK DAN ASAM AMINO PADA NATTO YANG DIFERMENTASI OLEH 7 STRAIN BACILLUS NATTO - JOKO SULISTYO (Research Center for Biology-Indonesian Institute of Sciences, 1986)
JOKO SUUSTYO. 1986. Analysis of organic acid and amino acid in natto fermented by 7 strains of Bacillus natto. Berita Biologi 3 (6): 277 - 282. The ability of seven strains of Bacillus natto produced a number of organic and amino acid components in natto were investigated. Raw, submerced and autoclaved soybeans for natto contained 1.15% 0.46% and 0.77% in organic acid and 0.19%, 0.30% and 0.30% in amino acid, while after fermentation those range were 0.36 - 0.90% in organic acid and 2.86 -6.08% in amino add. During submercing, autoclaving and fermenting, citric acid component decreased down very sharply to about one hundredth of starting level. While acetic,iso-butiric and iso-valeric components increased up to 84.92%, 96.60% and 95.87%, respectively. Mean while, glutamic acid, iso-leucine,leucine andphenylalanine components of amino acid increased up to 84.36%, 90.52%, 91.67% and 95.88%, respecti